Punca utama keresahan spiritual dalam penjagaan paliatif menurut perspektif psikologi agama / Hasimah Chik - Hasimah , Chik (2018)
Palliative care is a holistic care for patients suffering from critical illnesses and a slight expectation of complete cure due to medical practitional experience. Palliative care is an initiative to help patients from all aspects of life whether physical, spiritual, psychological and social. The discomfort causes disruption to the entire patient's quality of life. Spiritual distress is one of the common phenomena experienced by patient who is suffering from critical illness. Spiritual distress can cause various aspects affected, whether physical, spiritual, psychological, and social aspects. This study aimed to find out the factors that contribute to the spiritual distress in palliative patients. Starting by detecting the spiritual pain symptoms experienced by an individual, and then reviews their background the root causes of the problem, and the way they deal with and adapt to the problem. This study was carried out using a qualitative approach through a study of spiritual distress that occurred in palliative patients. Collecting data through library research to see the concept of spirituality from various religious beliefs, especially Islam, Christian, Buddhism, Hinduism and others. The main data of the study were obtained from palliative patients’ interviews and observation in Palliative Care wards. The findings show that problem of spiritual distress due to the unmet of spiritual need. The spiritual needs are based on the way people understand the meaning of the spirituality in life. Among the definitions of spirituality understood are religious, relationships with greater powers, values, individualistic, connectedness, life’s test and also negative aspects. Meanwhile the factors found to contribute to the condition of spiritual well-being or spiritual problem are the factors of life experience, family support, daily life routine, spiritual understanding, knowledge and personality factors. In spiritual distress coping, strengthen spiritual fundamental is essential to emphasize. Elements and practices of psychotherapy are suggested and recommended to applied in life, to bring back the tranquillity and spiritual self-strength.